Correlation Between Noise and Age to Housewive's Blood Pressure in Ambengan Surabaya Residence - Suryani, Novi Dwi Ira (JURNAL KESEHATAN LINGKUNGAN, 2018)
Noise is a physical exposure that effect to health such as increasing blood pressure. Therefore the aim of this research was to examine the correlation between noise and age toward housewive's blood pressure. This research applied cross-sectional study with observational comparative method. The population was housewives in Ambengan Surabaya residence with a sample of 53 people, including 29 study and 24 controls selected through cluster sampling. Noise, age, durration of exposure, family history of hypertension, consumption of coffee and salt selected to be independent variables. Noise data measured in the respondent house used Sound Level Meter Merk Kanomax Model 4020. The result of bivariat correlation used chi square showed that there was significant correlation between noise (p (0,002) < α(0.05)) and age (p (0.029) < α(0.05)) to housewive's blood pressure. It is conclued that noise and age related to housewive's blood pressure. Government requaired to socialize the damage and health effect of train noise levels to people who lives in residence surround railway and resettlement within < 6 meters from railway into larger land. At last, to ensure the presence of inferential causal temporality, it is required to conduct further study with design of cohort study in a larger sample and correlate variable.